2001
DOI: 10.1017/s1355838201010524
|View full text |Cite
|
Sign up to set email alerts
|

Functional selection of splicing enhancers that stimulate trans-splicing in vitro

Abstract: The role of exonic sequences in naturally occurring trans-splicing has not been explored in detail. Here, we have identified trans-splicing enhancers through the use of an iterative selection scheme. Several classes of enhancer sequences were identified that led to dramatic increases in trans-splicing efficiency. Two sequence families were investigated in detail. These include motifs containing the element G / C GAC G / C and also 59 splice site-like sequences. Distinct elements were tested for their ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 72 publications
1
20
0
Order By: Relevance
“…In the accompanying article, Boukis and Bruzik (2001) have used a randomization/selection protocol (SELEX) to identify exonic sequence elements that can promote trans-splicing in vitro+ Briefly, they introduced a randomized 18-nt sequence into a derivative of the "cis" 39 half molecule described above (see Fig+ 1)+ Although the starting pool was an inefficient substrate for transsplicing, several rounds of enrichment yielded discrete sequence elements that conferred a striking enhancement of trans-splicing (Boukis & Bruzik, 2001)+ We wished to determine if the elements identified by functional SELEX exerted their effects in a manner similar to the elements present in a naturally trans-spliced exon; that is, via promotion of 39 splice site recognition+ Two classes of enhancers were examined; the first contains repeats of the sequence G / C GAC G / C ; the second contains sequence elements that resemble a 59 splice site (Boukis & Bruzik, 2001)+ Figure 2 shows that the presence of either enhancer dramatically increased U2 snRNP binding relative to the enhancerless molecule; the level of U2 snRNP association is comparable to that seen with the naturally trans-spliced exon+ In this regard, the pattern of resistant fragments due to U2 snRNP binding observed with this molecule is altered somewhat from that seen with our wild-type substrate (i+e+, fragment sets I and II are replaced with a single fragment set I*)+ This difference is presumably due to the fact that the outron sequences of the two molecules diverge upstream of position Ϫ42+ It is unclear, however, how this sequence variation affects nuclease resistance+ Boukis and Bruzik (2001) have shown that the enhancement of trans-splicing conferred by the 59 splice site-like sequence is dependent upon U1 snRNP binding; that is, sequestration of the 59 end of U1 snRNA with an antisense oligonucleotide abrogated enhancement+ Importantly, occlusion of the 59 end of U1 snRNA prevented U2 snRNP binding to the molecule containing the 59 splice site-like enhancer (Fig+ 2, lane 18)+ FIGURE 2. Distinct types of exonic enhancers promote U2AF and U2 snRNP binding+ Four pre-mRNA substrates differing in exonic sequence were uniquely labeled between the A and G of the 39 splice site; the closed box indicates the "trans" exon as in Figure 1B These experiments further document the direct correlation between the ability of a 39 half-molecule to bind U2 snRNP and its ability to participate in trans-splicing+ Furthermore, three distinct types of exonic elements can function to promote U2 snRNP binding+ There are striking similarities between the 39 exonic requirements for trans-splicing we observe and those previously established by Chiara and Reed (1995) in their studies of bimolecular splicing in mammalian extracts+ They demonstrated that enhancers (either purine rich elements or a downstream 59 splice site) promoted formation of a stable complex at the 39 splice site and that such complexes could then participate in splicing+ The parallels between 39 splice site engagement in natural and experimentally derived trans-splicing systems contrast with the quite distinct mechanisms of 59 splice site recognition in the two systems (see Denker et al+, 1996 for discussion)+ Having established that U2 snRNP binding was directly correlated with competence for trans-splicing, we sought to define further the mechanism of exondependent U2 snRNP association+ We have previously demonstrated that binding of recombinant human U2AF to the 39 splice sit...…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In the accompanying article, Boukis and Bruzik (2001) have used a randomization/selection protocol (SELEX) to identify exonic sequence elements that can promote trans-splicing in vitro+ Briefly, they introduced a randomized 18-nt sequence into a derivative of the "cis" 39 half molecule described above (see Fig+ 1)+ Although the starting pool was an inefficient substrate for transsplicing, several rounds of enrichment yielded discrete sequence elements that conferred a striking enhancement of trans-splicing (Boukis & Bruzik, 2001)+ We wished to determine if the elements identified by functional SELEX exerted their effects in a manner similar to the elements present in a naturally trans-spliced exon; that is, via promotion of 39 splice site recognition+ Two classes of enhancers were examined; the first contains repeats of the sequence G / C GAC G / C ; the second contains sequence elements that resemble a 59 splice site (Boukis & Bruzik, 2001)+ Figure 2 shows that the presence of either enhancer dramatically increased U2 snRNP binding relative to the enhancerless molecule; the level of U2 snRNP association is comparable to that seen with the naturally trans-spliced exon+ In this regard, the pattern of resistant fragments due to U2 snRNP binding observed with this molecule is altered somewhat from that seen with our wild-type substrate (i+e+, fragment sets I and II are replaced with a single fragment set I*)+ This difference is presumably due to the fact that the outron sequences of the two molecules diverge upstream of position Ϫ42+ It is unclear, however, how this sequence variation affects nuclease resistance+ Boukis and Bruzik (2001) have shown that the enhancement of trans-splicing conferred by the 59 splice site-like sequence is dependent upon U1 snRNP binding; that is, sequestration of the 59 end of U1 snRNA with an antisense oligonucleotide abrogated enhancement+ Importantly, occlusion of the 59 end of U1 snRNA prevented U2 snRNP binding to the molecule containing the 59 splice site-like enhancer (Fig+ 2, lane 18)+ FIGURE 2. Distinct types of exonic enhancers promote U2AF and U2 snRNP binding+ Four pre-mRNA substrates differing in exonic sequence were uniquely labeled between the A and G of the 39 splice site; the closed box indicates the "trans" exon as in Figure 1B These experiments further document the direct correlation between the ability of a 39 half-molecule to bind U2 snRNP and its ability to participate in trans-splicing+ Furthermore, three distinct types of exonic elements can function to promote U2 snRNP binding+ There are striking similarities between the 39 exonic requirements for trans-splicing we observe and those previously established by Chiara and Reed (1995) in their studies of bimolecular splicing in mammalian extracts+ They demonstrated that enhancers (either purine rich elements or a downstream 59 splice site) promoted formation of a stable complex at the 39 splice site and that such complexes could then participate in splicing+ The parallels between 39 splice site engagement in natural and experimentally derived trans-splicing systems contrast with the quite distinct mechanisms of 59 splice site recognition in the two systems (see Denker et al+, 1996 for discussion)+ Having established that U2 snRNP binding was directly correlated with competence for trans-splicing, we sought to define further the mechanism of exondependent U2 snRNP association+ We have previously demonstrated that binding of recombinant human U2AF to the 39 splice sit...…”
Section: Resultsmentioning
confidence: 98%
“…All substrates were derived from either a naturally transspliced pre-mRNA or a cis-spliced intron (Hannon et al+, 1990(Hannon et al+, , 1991 and its accompanying 39 exon+ The substrate used in Figure 1A, lane 1, contained the 39-most 79 nt of the cis intron fused to the trans exon+ The substrate used in Figure 1A, lane 2, contained the same 79-nt intronic sequence fused to the cis 39 exon+ Substrates used in Figure 2 included a shortened derivative of the same cis intron/exon combination (lanes 6-10) and two pre-mRNAs derived by functional SELEX (Boukis & Bruzik, 2001; see legend to Fig+ 2)+ For analysis of splicing, RNAs were labeled with either [a-…”
Section: Pre-mrna Substratesmentioning
confidence: 99%
“…Several ACEs have been shown to have splicing enhancer activity (7,12,38), and a very similar sequence (CAATCAACA) is a nearly invariant feature of the nine 13-nt repeat elements found in the dsx and fru splicing VOL. 23,2003 tra2 DIRECTLY REPRESSES SPLICING 5179 enhancers ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in HeLa nuclear extracts it has been observed that the dsx 13-nt repeats act as constitutive splicing enhancers that bind SR proteins independently of Tra and Tra2 when moved to a position close to the dsx 3Ј splice site (44). A/C-rich sequences with enhancer activity have also been identified in both in vivo and in vitro selections of random sequences for those promoting exon inclusion in vertebrate cells (7,12,37). More recently it has been shown that activation of exon inclusion in the CD44 gene depends largely on an A/C-rich splicing enhancer that binds the Y box protein YB-1 (40) Mattox, and S. M. Berget, submitted for publication).…”
Section: Discussionmentioning
confidence: 99%
“…In Caenorhabditis elegans, trans-splicing is signaled by a 39ss without an upstream 59ss. Artificial trans-splice sites can be created from cis-splice sites by removing an upstream 59ss (Conrad et al 1991(Conrad et al , 1995Maroney et al 2000;Boukis and Bruzik 2001), and a trans-splice site can be made to cis-splice instead by insertion of a 59ss into the outron, the intronlike sequence upstream of the trans-splice site (Conrad et al 1993).…”
mentioning
confidence: 99%